Advanced Materials used for different components of Gas Turbine (International Journal of Scientific Research and Management (IJSRM), 2013)
Design of Turbo machinery is complex and efficiency is directly related to material performance, material selection is of prime importance. Temperature limitations are the most crucial limiting factors to gas turbine efficiencies. The problems at various components are of different magnitudes. As a result, the materials selection for individual components is based on varying criteria in gas turbines. Also materials and alloys for high temperatures application are very costly. This paper is focused on the study of various materials for their applicability for different components of gas turbine for increasing the performance, reliability and emissions in gas turbines. This paper presents a critical review of the existing literature of gas turbine materials. The paper will focus light on above issues and each plays an important role within the Gas Turbine Material literature and ultimately influences on planning and development practices. It is expected that this comprehensive contribution will be very beneficial to everyone involved or interested in Gas Turbines.